The Distribution and Origin of Carbonate Cements in Deep-Buried Sandstones in the Central Junggar Basin, Northwest China. (14th September 2017) - Furong, Wang; Sheng, He; Yuguang, Hou; Tian, Dong; Zhiliang, He
Abstract : Extremely high porosities and permeabilities are commonly discovered in the sandstones of the Xishanyao Formation in the central Junggar Basin with the burial depth greater than 5500 m, from which hydrocarbons are currently being produced. High content of carbonate cements (up to 20%) is also observed in a similar depth range. Our study aimed to improve our understanding on the origin of carbonate cements in the Xishanyao Formation, in order to provide insights into the existence of high porosity sandstones at greater depths. Integrated analyses including petrographic analysis, isotopic analysis, fluid-inclusion, and core analysis were applied to investigate the distribution and origin of carbonate cements and the influence of high fluid pressure on reservoir quality. Textural evidences demonstrate that there are two generations of carbonate cements, precipitated at the temperature of 90°C and 120°C, respectively. The carbonate cements with low δ C P D B 13 ranging from −19.07 to - 8.95 ‰ dominantly occurred near the overpressure surface and especially accumulated at approximately 100 m below the surface. Our interpretation is that high content of carbonate cements is significantly influenced by early carbonate cements dissolution and migration under overpressure. Dissolution of plagioclase resulted in the development of internal pores and porosities of as much as 10% at 6500 m depth presumably.